E-012 Urgent intra-arterial thrombectomy for stroke: technical complications. (4th July 2012) - de Miquel, M; Aja, L; Mora, P; Aixut, S; Cardona, P; Quesada, H; Rubio, F; Barranco, R
Abstract : Introduction: Since April 2010, a pilot experience has been set for offering intra-arterial treatment for stroke to a 3.5 million people population. We aim to share our experience from the standpoint of technical complications. Material and Methods: The review of 122 patients (69 male and 53 female, mean age 65, 4 years) show that twelve cases presented technical complications. In four patients, distal emboli to other territories than the occluded vessel were seen. Two of them were not specifically treated and showed a bad outcome, while the other two were successfully treated with good final Rankin Score. Hemorrhage during microcateterization was noted in four patients. Even though the bleeding was controlled with glue or coils, bad outcome was noted in those patients. One patient presented a femoral pseudoaneurysm related to the puncture site, with severe bleeding and other co-morbidity leading to death. Carotid stent issues in tandem lesions were seen in two patients. In one case, the thrombectomy device was let in place (M1) due to impossibility to retrieve it. Some subclinical incidences as balloon rupture (1 case), M1, M2 or M3 vasospasm, easily resolved with intraarterial nimodipine (3 cases) and some degree of vessel dissection without significant caliber reduction (3 cases) were also recorded. Results and Conclusion: In our series, around a ten percent of intraarterial thrombectomy treatments presented procedure related complications. In our opinion, four of them can be attributed to our learning curve, leading to a theoretical complication risk of around a 7% for technical complications. Competing interests: None.